Charles Willson Peale’s The Exhumation of the Mastodon and the Great Chain of Being: The Interaction of Religion, Science, and Art in Early-Federal America - Zygmont, Bryan J. (Text Matters: A Journal of Literature, Theory and Culture, 2015)
Although primarily known as a portrait painter, Charles Willson Peale (1741-1827) also possessed a profound interest in natural history. Indeed, Peale eventually founded the first natural history museum in the United States, and, during the end of the eighteenth century, he began to overlap his two great interests: art and nature. The event Peale chronicled in his 1804 painting The Exhumation of the Mastodon caused an extreme stir within the intellectual and religious circles of its time, and brought about, at the very least, a serious questioning in the deeply held notion of the Great Chain of Being. Although now largely discredited, this religious conviction postulated two concepts that Peale’s Exhumation of the Mastodon seemingly contradicts. The first was the belief that no animals since creation had suffered the fate of extinction. The second was a lack of belief in geological time. Indeed, one Irish clergyman calculated the actual date of creation to 4004 BCE. In this paper, I explore Peale’s monumental painting, a work that is many things, a self-portrait and history painting among others. Indeed, in this painting, Peale was responding to science, religion, and their shifting positions within early-nineteenth-century America. When viewed together, Peale’s The Exhumation of the Mastodon is not merely a record of an event that occurred in New York during the early nineteenth century, and instead is a document of Peale and the interaction of science and religion in early-Federal America.